2014
DOI: 10.1111/j.2047-2927.2014.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to testis cancer chemotherapeutics alters sperm fertilizing capacity and affects gene expression in the eight-cell stage rat embryo

Abstract: Treatment of testicular cancer includes the coadministration of bleomycin, etoposide and cis-platinum (BEP); however, along with its therapeutic benefit, BEP exposure results in extensive reproductive chemotoxic effects, including alterations to sperm chromatin integrity. As an intact paternal genome is essential for successful fertilization and embryogenesis, we assessed the effect of paternal exposure to BEP on sperm fertilization capacity and the resulting consequences on early embryonic gene expression. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Finally, there are two subjects that must be emphasized here: (i) The exposure to chemotherapeutic drugs may cause adverse effects on the progeny (Hales et al ., ); and (ii) an intact paternal genome is essential for successful fertilization and embryogenesis (Maselli et al ., ). In the present research, the quality and viability of early embryos were not evaluated, but the results of reproductive capacity showed that doxorubicin increased the embryonic loss in comparison to control rats; nevertheless, carnitine administered alone or previously to doxorubicin did not significantly cause any harmful alteration in the reproductive parameters covered by our studies, but it improved some of them.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, there are two subjects that must be emphasized here: (i) The exposure to chemotherapeutic drugs may cause adverse effects on the progeny (Hales et al ., ); and (ii) an intact paternal genome is essential for successful fertilization and embryogenesis (Maselli et al ., ). In the present research, the quality and viability of early embryos were not evaluated, but the results of reproductive capacity showed that doxorubicin increased the embryonic loss in comparison to control rats; nevertheless, carnitine administered alone or previously to doxorubicin did not significantly cause any harmful alteration in the reproductive parameters covered by our studies, but it improved some of them.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, alteration in sperm acrosomal integrity in cyclosporinetreated group suggests a reduction in the spermatozoa's fertilization capacity of the rats. The ability of lutein to normalize the altered ALP, ACP, sialic acid content as well as sperm acrosomal integrity however, suggests improvement in acrosomal integrity, decreased cellular stress and enhanced spermatogenesis (Maselli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here, AR sperm exhibited a drop in HSP90AA1 protein levels. HSP90AA1 is a ubiquitously expressed chaperone protein that aids in protein transport, assembly, and folding, , localizing to the flagellum and head of sperm cells. , HSP90AA1 is an important regulator of diverse cellular processes including ROS scavenging, apoptosis, ATP metabolism, and sperm motility . These different activities may shape the role played by HSP90AA1 in the setting of sperm AR induction.…”
Section: Discussionmentioning
confidence: 99%